Monster Hunter Alpha - Correia, Larry (Riverdale, NY : Baen, 2011)
"Earl Harbinger may be the leader of Monster Hunter International, but he's also got a secret. Nearly a century ago, Earl was cursed to be a werewolf. When Earl receives word that one of his oldest foes, a legendarily vicious werewolf that worked for the KGB, has mysteriously appeared in the remote woods of Michigan, he decides to take care of some unfinished business. But another force is working to bring about the creation of a whole new species of werewolf. When darkness falls, the final hunt begins, and the only thing standing in their way is a handful of locals, a lot of firepower, and Earl Harbinger's stubborn refusal to roll over and play dead"-- Publisher.
Keywords: Werewolves -- Fiction; Monsters -- Fiction; Fantasy fiction